2023
DOI: 10.1002/jnr.25172
|View full text |Cite
|
Sign up to set email alerts
|

In vivo imaging of nitric oxide in the male rat brain exposed to a shock wave

Abstract: While numerous studies have suggested the involvement of cerebrovascular dysfunction in the pathobiology of blast‐induced traumatic brain injury (bTBI), its exact mechanisms and how they affect the outcome of bTBI are not fully understood. Our previous study showed the occurrence of cortical spreading depolarization (CSD) and subsequent long‐lasting oligemia/hypoxemia in the rat brain exposed to a laser‐induced shock wave (LISW). We hypothesized that this hemodynamic abnormality is associated with shock wave‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Examining the long-term ramifications of exposure to LLB is particularly significant due to its potential to contribute to chronic deficits in cerebral perfusion by accelerating aging-related mechanisms in cerebrovascular dysfunction, such as reductions in nitric oxide (NO) availability and neurovascular oxidative stress [ 108 ]. Notably, preclinical investigations have demonstrated that blast exposure triggers acute oxidative stress [ 21 , 44 , 60 , 109 , 110 ] and alters NO production [ 60 , 111 , 112 ], linking both to disruptions in BBB permeability [ 44 , 109 , 111 , 112 , 113 ]. Intriguingly, similar patterns of neurovascular dysfunction are apparent in neurodegenerative diseases, such as AD, dementia, and PD [ 100 ].…”
Section: Cellular Underpinnings Of Progressive Perfusion Deficits Aft...mentioning
confidence: 99%
“…Examining the long-term ramifications of exposure to LLB is particularly significant due to its potential to contribute to chronic deficits in cerebral perfusion by accelerating aging-related mechanisms in cerebrovascular dysfunction, such as reductions in nitric oxide (NO) availability and neurovascular oxidative stress [ 108 ]. Notably, preclinical investigations have demonstrated that blast exposure triggers acute oxidative stress [ 21 , 44 , 60 , 109 , 110 ] and alters NO production [ 60 , 111 , 112 ], linking both to disruptions in BBB permeability [ 44 , 109 , 111 , 112 , 113 ]. Intriguingly, similar patterns of neurovascular dysfunction are apparent in neurodegenerative diseases, such as AD, dementia, and PD [ 100 ].…”
Section: Cellular Underpinnings Of Progressive Perfusion Deficits Aft...mentioning
confidence: 99%